Pelanggaran Ham Dalam Konflik Israel dan Palestina - Lewiandy, Lewiandy; Alessandro Christian Max (LPPM Universitas Ekasakti Padang, 2024)
All human beings have human rights not because of a gift given to them, but a gift given by the Creator to every human being. Any human being does not have the right to deprive each other of their rights, if this happens then that person will also be called a human rights violator. As is happening now, Israel's human rights violations against Palestinians are a taking away of other people's rights, especially the right to live and live in safety. Even though there is international law that protects cases of human rights violations, ironically humanitarian tragedies still occur. The results of this research found that attacks carried out by the Israeli army had destroyed many residences, places of worship and other public facilities in Palestine. Most countries in all other parts of the world, especially countries with predominantly Muslim populations, strongly condemn all forms of actions committed by the Israeli army against Palestine. Israel is also stated to have violated human rights, this has been going on for a long time and continuously until now, which is happening to Palestinians.